Penentuan Kebutuhan Air Irigasi Optimum dengan beberapa Alternatif Pola Tata Tanam pada Daerah Irigasi Semalat - Handriyati , Mimie Try ; Khaerudin , Dian Noorvy ; Sulistyani, Kiki Frida (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Semalat Irrigation Area (DI) is an irrigation area located in Sungai Betung District, Bengkayang Regency, West Kalimantan Province with an area of 51.91 hectares. So far, there has been no determination of optimum cropping patterns in accordance with agricultural conditions in Semalat. Therefore, there is a need for research on an analysis of the determination of optimum planting patterns from several alternatives. Determination of the optimum planting system pattern aims to maximize agricultural land that is irrigated by irrigation so as to obtain increased crop yields with the need for efficient irrigation water. The choice of a number of alternative planting patterns is based on the time of the start of the planting period. There are five alternative cropping patterns proposed in the Semalat Irrigation Area, the first is the existing cropping pattern by starting the first rice planting on November 1, the first alternative by starting the first rice planting on October 15, the second alternative by starting the first rice planting in November 15, the third alternative by starting the first rice planting on December 1, and the fourth alternative by starting the first rice planting on December 15. Of the five alternatives proposed in Semalat, the optimum cropping pattern is the existing cropping pattern starting with the first rice planting on November 1 with a total irrigation water requirement for 51.91 hectares of rice field area is 86.17 lt / sec / ha.